2020
DOI: 10.1111/jdi.13441
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and adverse maternal and perinatal outcomes for women with dichorionic twin pregnancies complicated by gestational diabetes mellitus: A retrospective cross‐sectional study

Abstract: Aims/Introduction The association between gestational diabetes mellitus (GDM) and adverse maternal and perinatal outcomes in twin pregnancies remains unclear. This study was undertaken to highlight risk factors for GDM in women with dichorionic (DC) twins, and to determine the association between GDM DC twins and adverse maternal and perinatal outcomes in a large homogeneous Taiwanese population. Materials and Methods A retrospective cross‐sectional study was carried out on 645 women with DC twins, excluding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…Based on the IADPSG criteria, we obtained a prevalence similar to that reported in another Chinese population with twin pregnancies (20.4%) ( 30 ). In line with previous reports ( 14 , 15 , 23 , 31 ), women with GDM were of advanced age and higher BMI. Conversely, our finding, that the incidence of PIH or PE between GDM and non-GDM women was similar, was conflicting with previous studies, which reported a relationship between GDM and HDP in both singleton and twin pregnancies ( 15 , 21 , 32 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the IADPSG criteria, we obtained a prevalence similar to that reported in another Chinese population with twin pregnancies (20.4%) ( 30 ). In line with previous reports ( 14 , 15 , 23 , 31 ), women with GDM were of advanced age and higher BMI. Conversely, our finding, that the incidence of PIH or PE between GDM and non-GDM women was similar, was conflicting with previous studies, which reported a relationship between GDM and HDP in both singleton and twin pregnancies ( 15 , 21 , 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the current evidence on the outcomes among GDM twin pregnancies is limiting and conflicting. Some authors have reported that GDM twin pregnancies have similar outcomes with non-GDM ones ( 14 , 15 ) whereas others have found GDM twin pregnancies with GDM have increased risks of adverse outcomes, including cesarean section ( 16 18 ), hypertensive complications ( 19 22 ), accelerated fetal growth ( 22 24 ) and neonatal respiratory morbidity ( 18 ). The conflicting findings may be due to several limitations including relatively small population, inadequate adjustment for confounders, and lack of addressing the intertwin correlation when analyzing neonatal outcomes ( 16 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly caused by greater use of assisted reproductive technology and shift toward an older maternal age [2].Unfortunately twin pregnancy is also associated with a higher complication rate compared to singleton pregnancy. Women with twin pregnancy are exposed to miscarriage, gestational diabetes mellitus (GDM), hypertension, anemia, placenta previa, placental abruption, preterm labour, premature rupture of membranes [2,7,8]. The growing prevalence of GDM and twin pregnancy has given rise to their increasing concurrent presentation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The growing prevalence of GDM and twin pregnancy has given rise to their increasing concurrent presentation [3]. Some studies have shown an increased risk for gestational hypertension, preeclampsia, cesarean section in women with twin pregnancy and GDM compared to women with twin pregnancy without GDM [8]. The aim of our study is to assess whether the increased risk associated with twin pregnancy is exacerbated in the presence of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although available evidence is limited, several studies have shown that GDM in twin pregnancy is associated with similar adverse maternal and neonatal outcomes than that in singleton pregnancy. [9][10][11] Choline is an essential nutrient necessary for the integrity of cell membranes, cholinergic neurotransmission and one-carbon metabolism. 12 In one-carbon metabolism, choline is irreversibly oxidized to betaine, which donates its methyl group in the remethylation of homocysteine to methionine, a reaction generating dimethylglycine (DMG) 13 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%